2022
DOI: 10.3390/sym14010167
|View full text |Cite
|
Sign up to set email alerts
|

Research on Influence Factors of Bearing Capacity of Concrete-Filled Steel Tubular Arch for Traffic Tunnel

Abstract: When a traffic tunnel passes through special strata such as soft rock with high geo-stress, expansive rock, and fault fracture zones, the traditional supporting structure is often destroyed due to complicated loads, which threatens the construction and operation safety of tunnel engineering. Concrete-filled steel tubular (CFST) structure gives full play to the respective advantages of steel and concrete and has better bearing capacity and economic benefits than traditional support structure, which has achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The steel tube at the arch foot will uplift obviously and the hoop action of the steel pipe on the concrete will fail when the CFST arches reach the ultimate bearing capacity. Li and Lei (2022) studied the influencing factors of the bearing capacity of CFST arches by numerical simulation and found that the arch had a great limitation on displacement in the elastic stage, and the ultimate bearing capacity was relatively high. The bearing capacity decreases obviously after reaching the peak value, but it showed good elongation performance.…”
Section: Introductionmentioning
confidence: 99%
“…The steel tube at the arch foot will uplift obviously and the hoop action of the steel pipe on the concrete will fail when the CFST arches reach the ultimate bearing capacity. Li and Lei (2022) studied the influencing factors of the bearing capacity of CFST arches by numerical simulation and found that the arch had a great limitation on displacement in the elastic stage, and the ultimate bearing capacity was relatively high. The bearing capacity decreases obviously after reaching the peak value, but it showed good elongation performance.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of these concrete-filled steel tube (CFST) structures have been investigated by numerous researchers in the technical literature. [7][8][9][10] Packer 11 tested rectangular CFST connections, where substantial strength enhancement was seen when the infill concrete was involved. Liu et al 12 experimented with the impact of infill concrete in circular hollow section (CHS) and rectangular hollow section (RHS) steel tube elements.…”
Section: Introductionmentioning
confidence: 99%